2013
DOI: 10.1007/s12598-013-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Grain and dendrite refinement of A356 alloy with Al–Ti–C–RE master alloy

Abstract: Commercial A356 alloy was refined with a homemade Al-5Ti-0.25C-2RE master alloy, and the microstructure and macrostructure of the refined alloy were investigated. The results show that the grain refining effect of A356 is poor by the addition level of 0.5 wt% master alloy, but when the level reaches 3.0 wt% the grain can get a satisfactory refining effect. Dendrite of A356 can be effectively refined by addition of 0.5 wt% master alloy; however, the refining effect is not significantly improved by further incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…By melts modifications with special compounds or elements, the microstructure can be greatly improved. For examples, the TiB 2 , TiC, Al 3 Sc, Al 3 Y, and Al 3 Er compounds serve as heterogeneous nucleation sites to facilitate the nucleation of α-Al crystals [3,6,11,13,30,31]; some active elements adsorbing on the surface of the primary α-Al dendrites advance their flourishing growth due to constitutional supercooling [8,32]. On the other hand, elements such as Sr, P, Na, and RE adsorb on the surface of the eutectic Si phases to inhibit the orientation growths along {200}, {110}, or {101} planes, resulting in short rods or even small granules [13,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…By melts modifications with special compounds or elements, the microstructure can be greatly improved. For examples, the TiB 2 , TiC, Al 3 Sc, Al 3 Y, and Al 3 Er compounds serve as heterogeneous nucleation sites to facilitate the nucleation of α-Al crystals [3,6,11,13,30,31]; some active elements adsorbing on the surface of the primary α-Al dendrites advance their flourishing growth due to constitutional supercooling [8,32]. On the other hand, elements such as Sr, P, Na, and RE adsorb on the surface of the eutectic Si phases to inhibit the orientation growths along {200}, {110}, or {101} planes, resulting in short rods or even small granules [13,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The affect of TiC together with Al 3 Ti granulation on the heterogeneous nucleation of α-Al pellet has been covered together with verified by other researchers [16][17][18]. It has been reported that Ti 2 A1 20 RE can not exist stably in the aluminum alloy melt [19,20], it will dissolve and provide a lot of RE for the aluminum melt [21]. A large number of research reports have confirmed that RE has a good modification effect on eutectic Si by forming nano rare earth phase [22] or inhibiting Si twin growth [23].…”
Section: Resultsmentioning
confidence: 69%
“…Composites are formed by reinforcing the ceramic particles in the melt [7][8]. Through various research articles, it is illustrated that the improvement in mechanical properties is observed due to the reinforcing of various ceramic particles like Al2O3, SiC, B4C, TiC and TiB2 etc [9][10][11]. The traditional electromagnetic stir casting process is used to develop the aluminum metal matrix composite.…”
Section: Introductionmentioning
confidence: 99%